Jakość energii elektrycznej - Kowalski, Zbigniew (Wydawnictwo Politechnika Łódzka, 2007)
The book includes basie information concerning the quality of electrical energy in ac systems. It describes the features and parameters of the electrical energy quality and provides the characteristics of the following electrical energy features: frequency, voltage, current and electrical power. The publication presents the quality parameters of ac electrical energy concernmg: - deviations and fluctuations of voltage and current frequency, - voltage deviations, - voltage fluctuations, - voltage dips and swells, - transient overvoltages, - current and voltage asymmetry, - current and voltage distortions, - power distortion. With reference to the presented parameters the following aspects are analysed: the parameter definitions, the origins of the phenomena described by the above parameters and their effects, standard requirements and the correction methods of inappropriate parameter values. The book also includes information on statistical characteristics of electrical energy quality parameters and a brief overview of the parameter measurement methods.
Książka jest przeznaczona przede wszystkim dla studentów wydziałów elektrycznych wyższych uczelni, a w szczególności studentów i dyplomantów studiujących specjalności dotyczące przesyłu, rozdziału i użytkowania energii elektrycznej.
Red. serii : Wodziński, Piotr
Keywords: energia elektryczna; jakość energii elektrycznej; prąd przemienny; wahania napięcia; electricity; quality of electricity; alternating current; voltage fluctuations